2007
DOI: 10.1590/s0066-782x2007001700003
|View full text |Cite
|
Sign up to set email alerts
|

Doença arterial coronariana em diabéticas do tipo 2 assintomáticas: estudo comparativo entre o teste ergométrico, o teste cardiopulmonar e a cintilografia de perfusão miocárdica com dipiridamol na identificação de isquemia

Abstract: SummaryBackground: Cardiovascular disease is the leading cause of morbidity and mortality among diabetic individuals. Myocardial ischemia is frequently asymptomatic, thus leading to a late diagnosis and worse prognosis. Diabetic women are known to have a cardiovascular death risk higher than that in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Such data are in accordance with those of the literature. Smanio et al 11 , studying the MPS of 104 asymptomatic diabetic women, have reported myocardial ischemia in 34 (32.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such data are in accordance with those of the literature. Smanio et al 11 , studying the MPS of 104 asymptomatic diabetic women, have reported myocardial ischemia in 34 (32.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise testing is known to have lower sensitivity and specificity in the female sex than in the male sex 18 . The sensitivity and specificity of the pharmacological or exercise stress tests can be improved by imaging methods that increase diagnostic accuracy 10,11,18 . With the refinement of the technique, a reduction in attenuation artifacts (breast, for example) was observed, leading to greater specificity 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation